THE IMPACT OF FAMILY AND SOCIETY ON INCLUSIVE EDUCATION - Rakhimova Khurshidakhon Sadikovna; Oʻktamova Muxtasar Ravshanbek qizi (Journals Park Publishing, 2025)
This article explores inclusive education and its impact on society, as well as the role of families and communities in the education system. The importance of collaboration between the state, society, and families in the development of inclusive education is emphasized. The article describes the support of parents for inclusive education, their attitudes toward their children, and the public perception of this system. It highlights the necessity of family and community readiness for inclusive education, the preparation of pedagogical staff, the improvement of schools’ material and technical resources, and the creation of a supportive social environment for children with disabilities.
Keywords: Inclusive education, Society, Family, Education system, Children with disabilities, Special educational needs, Equal opportunities, Parental role, Social justice, Child development, Special needs, Concept of inclusive education.